Overview - issues and challenges for freight logistics industry in Malaysia - Kim, Yoke Ong; Zailani, Suhaiza; Kanapathy, Kanagi (UUM College of Business, 2020)
In Malaysia, majority of the freight logistics companies has placed priority in enhancing their operational performances and its sustainable competitiveness. Ten (10) preliminary face-to-face interviews have been conducted. The informants have been selected based on the researcher’s network using the snowballing techniques. The purpose of this paper intents to review the issues and challenges faced by freight logistics companies in Malaysia: Logistics Performance Index, Container Deposits Payment, Freight Logistics Workforce and Employment Compensation, Logistic Social Responsibility. The researchers have conveyed these 4 issues and challenges influencing the freight logistics operational performances in Malaysia. The freight logistics risks management model has provided a base for the future researcher in examining the relevant relationships empirically.